A new tool for self-evaluation of adherence to antimuscarinic drugs treatment in patients with urinary incontinence - Kirill V. Kosilov (Taylor & Francis Group, 2017)
Abstract objective: To evaluate the validity of the Medication Adherence Self-Report Inventory (MASRI) questionnaire in determining antimuscarinic drugs adherence in patients with urinary incontinence (UI). Patients and methods: In all, 629 patients [355 (56.4%) women and 274 (43.6%) men], aged 18â65â¯years, were included. All patients were prescribed antimuscarinic drugs and treatment adherence was tested at the start, and after 4, 8 and 12â¯weeks using the MASRI. The standard of external monitoring was the Brief Medication Questionnaire (BMQ) and visual count of the remaining pills. The functional status of the lower urinary tract was tested using voiding diaries and uroflowmetry. Results: The correlation between indicators of adherence according to the MASRI and screen mode of the BMQ was râ¯=â¯0.84 (Pâ¯â¤â¯0.01), râ¯=â¯0.72 (Pâ¯â¤â¯0.01), râ¯=â¯0.7 (Pâ¯â¤â¯0.05) at 4, 8 and 12â¯weeks of follow-up, respectively, which indicated a satisfactory competitive validity. In the study of the discriminant validity, we found that non-adherent patients were correctly identified according to the MASRI in 96.2%, 96.9% and 96.2% of cases at 4, 8 and 12â¯weeks of follow-up, respectively. The values of the positive likelihood ratio (7.92, 10.81, and 12.8 at 4, 8 and 12â¯weeks of follow-up, respectively) were quite acceptable for the adherence forecast. The receiver operating characteristic analysis revealed a failure of the null hypothesis of the excess/insufficient discrimination power of the MASRI. The correlation between the percentage of non-adherent patients and the percentage of patients with impaired lower urinary tract function according to uroflowmetry data was râ¯=â¯0.55 (Pâ¯â¤â¯0.05) at 4â¯weeks; râ¯=â¯0.59 (Pâ¯â¤â¯0.05) at 8â¯weeks; and râ¯=â¯0.62 (Pâ¯â¤â¯0.01) at 12â¯weeks. Conclusion: The MASRI questionnaire is highly constructive, competitive, has discriminant validity, and is suitable for self-assessment of treatment adherence in patients with UI taking antimuscarinics. Using the MASRI is less costly and faster compared with other assessment tools. Keywords: Self-evaluation, Questionnaire, Antimuscarinic, Adherence, Urinary incontinence